Peningkatan Kesadaran Lingkungan Melalui Pembuatan Tempat Sampah Daur Ulang Di RT.21 RW.02 Kelurahan Pematang Gubernur - Agresti, Agresti; Nisa, Nabela Aulia; Nabila, Melane Neysha; Anggraini, Adinda Dewi; Apiska, Nia; Herlin, Herlin; Susanti, Neri; Fitriano, Yun (Universitas Dehasen Bengkulu, 2025)
A clean environment is a basic necessity for society. However, suboptimal waste management still occurs at Raudhatul Jannah Mosque, located in RT.21 RW.02, Pematang Gubernur Subdistrict. Unsorted waste leads to pollution and decreases the comfort of worshippers. This community service program is part of the Kuliah Kerja Nyata (KKN) student community service activity, aiming to raise public awareness by creating recycled waste bins from used materials and placing them in the mosque area. The activities included awareness sessions, training on waste bin production, and observation of behavioral change. The results showed increased community knowledge regarding waste sorting and concern for the mosque's cleanliness. This program successfully fostered new, environmentally friendly habits through educational and participatory approaches.